Flow analysis of airfoil having different cavities on its suction surface. (2016) - Vuddagiri, Aswin; Halder, Paresh; Samad, Abdus; Chaudhuri, Abhijit
The paper presents the fluid flow analysis of a symmetric airfoil having circular cavities on its suction surface at three different chordwise locations from leading to trailing edges. The leading edge cavity shapes were distorted using Bezier polynomial so that vortex trapping pattern in the cavities can be captured. Structured meshing scheme via a multi-block strategy was employed. Unsteady simulations were performed by a Reynolds averaged Navier-Stokes (RANS) solver. Lift, drag, pressure and skin friction coefficients were monitored at Reynolds number (Re) = 15 × 10 4 and 6 × 10 5 and different angles of attack. Cavity placed at the trailing edge produced better lift to drag ratio as compared to that of the other cavities. The distorted cavities performed badly in terms of lift and drag coefficients. The elliptical cavity shape showed better results at the angles of attack up to 10°.